Concentration‐dependent, dual roles of IL‐10 in the osteogenesis of human BMSCs via P38/MAPK and NF‐κB signaling pathways. Issue 9 (9th April 2018) - Chen, Erman; Liu, Guanyi; Zhou, Xiaopeng; Zhang, Wei; Wang, Cong; Hu, Dongcai; Xue, Deting; Pan, Zhijun
ABSTRACT: Microenvironmental conditions can influence the differentiation and functional roles of mesenchymal stem cells (MSCs). Recent studies have suggested that an inflammatory microenvironment can significantly affect the osteogenic differentiation of MSCs. Here, we show, for the first time, that IL‐10 has concentration‐dependent, dual roles in the osteogenesis of human bone marrow mesenchymal stem cells (hBMSCs). Low physiologic concentrations of IL‐10 (0.01–1.0 ng/ml) activate the p38/MAPK signaling pathway to promote the osteogenesis of hBMSCs, but higher pathologic doses of IL‐10 (10–100 ng/ml) inhibit p38/MAPK signaling by activating NF‐κB, inhibiting osteogenesis. These results demonstrate that p38/MAPK and NF‐κB signaling mediates the double‐edged sword effect of IL‐10 on hBMSCs. The osteogenic impairment was reversed at higher doses of IL‐10 when cells were supplemented with the NF‐κB inhibitor BAY11–7082. These data provide important insights into the regulatory effects of IL‐10 on the biologic behavior of hBMSCs.—Chen, E., Liu, G., Zhou, X., Zhang, W., Wang, C., Hu, D., Xue, D., Pan, Z. Concentration‐dependent, dual roles of IL‐10 in the osteogenesis of human BMSCs via P38/MAPK and NF‐κB signaling pathways. FASEB J. 32, 4917–4929 (2018). www.fasebj.org